2020
DOI: 10.20511/pyr2020.v8nspe1.500
|View full text |Cite
|
Sign up to set email alerts
|

La filmación de clase en contexto de colegialidad: estrategia que favorece los procesos reflexivos respecto de la práctica pedagógica

Abstract: Este artículo se distribuye bajo licencia CC BY-NC-ND 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Similarly, Nocetti de la Barra and Medina Moya (2018) revealed that watching videos generates a bidirectional reflective experience; that is, not only the person presenting but also the person watching the video reflects on the practice. Accordingly, creating experiences in which teachers watch videos of their own practice enables them to focus more on students and their learning (Tripp & Rich, 2012), and to rediscover their professional functioning that could help them become aware of their own way of teaching, and of what they know, and what they do as teachers, thus bringing them closer to an epistemology that underlies classroom practice (Borquez-Mella et al, 2020).…”
Section: Video-mediated Strategy For Promoting Reflection On Educatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Nocetti de la Barra and Medina Moya (2018) revealed that watching videos generates a bidirectional reflective experience; that is, not only the person presenting but also the person watching the video reflects on the practice. Accordingly, creating experiences in which teachers watch videos of their own practice enables them to focus more on students and their learning (Tripp & Rich, 2012), and to rediscover their professional functioning that could help them become aware of their own way of teaching, and of what they know, and what they do as teachers, thus bringing them closer to an epistemology that underlies classroom practice (Borquez-Mella et al, 2020).…”
Section: Video-mediated Strategy For Promoting Reflection On Educatio...mentioning
confidence: 99%
“…Similarly, some studies have stated that, in addition to the reflective potential of watching videos, this strategy also stands out for promoting research on classroom practice (Tenorio Troncoso & López Norena, 2018), and identifying and underpinning teaching activities, elements that are essential for gaining theoretical knowledge and building practical knowledge (Borquez-Mella et al, 2020). MoEoC (n.d.-a), acknowledge that the video-mediated strategy promotes collaborative work in schools and encourages professional teacher training.…”
Section: Video-mediated Strategy For Promoting Reflection On Educatio...mentioning
confidence: 99%